Impact of domestic white LED light on cognitive functions and amelioration of blue light blocking lens (BBL) on healthy adults - Mousumi Ghosh; Hari Prakash Palaniswamy; Nishitha. G; Stelyna Joylin; Shwetha. T.S; M. Sanjana; R.P. Radhika; Nagarajan Theruveethi (Neurobiology of Sleep and Circadian Rhythms)
White light-emitting diodes (WLEDs) can affect cognition and working memory. Blue light-blocking lenses (BBL) may help alleviate this. We aim to study the relationship between WLED and the ameliorative effect of BBL. We included 15 healthy participants based on the PSQI and Mini-Cog™ screening. The eligible participants underwent a baseline recording of event-related potential (ERP) of P300 using electroencephalography (EEG) while performing a 2-back task, followed by exposure to WLED (600 lux) that was given (45° with 80 cm apart from the participant's eye plane) for 30 min. A similar protocol was maintained when BBL was worn with WLED exposure. The participants' mean PSQI and Mini-Cog™ scores (n = 15) were 3 and 5, respectively. The behavioral functioning of participants using a 2-back task revealed enhancement in working memory cognition by fastening the response time (ms) from base to post-WLED to post-WLED + BBL (p < 0.001). Still, no significant difference (p > 0.05) in accuracy (%) was observed. The learning effect in the control group using a 2-back task revealed no statistically significant difference (p > 0.05) in both accuracy (%) and response time (ms). Additionally, no significant change (p > 0.05) was found within the three light groups in latency (ms) and amplitude (μV) at the P300 region of ERP in the prefrontal cortex. The existing results found that domestic WLED exposure significantly leads to a faster response time in working memory performance in the prefrontal cortex, thus remaining alert. BBL is not protective in the nonvisual senses when exposed to WLED for 30 min.